1997
DOI: 10.1136/thx.52.6.563
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of plasma D-dimer levels in patients with lung cancer

Abstract: Abstractprotein components of the extracellular matrix, activate latent enzymes such as type IV colBackground -The peripheral blood concentrations of several proteases of the clot-lagenase, and dissolve tumour associated fibrin clots. 2 Circulating markers of the fibrinolysis ting system have been shown to predict survival in patients with malignancy. A system are raised in patients with lung cancer and they have been shown to correlate with study was undertaken to investigate the independent value of the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 19 publications
3
50
0
1
Order By: Relevance
“…7 In addition, changes in the clotting/fibrinolytic system in lung carcinoma patients are common. 3,9,[11][12][13][14][15][16][17] Clinical and experimental evidence supports the idea that the activation of coagulation/fibrinolysis may play an important role in the invasiveness of cancer. 6,7 For example, Kwaan and Keer 6 demonstrated a correlation between coagulation changes and the natural history of malignancies.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…7 In addition, changes in the clotting/fibrinolytic system in lung carcinoma patients are common. 3,9,[11][12][13][14][15][16][17] Clinical and experimental evidence supports the idea that the activation of coagulation/fibrinolysis may play an important role in the invasiveness of cancer. 6,7 For example, Kwaan and Keer 6 demonstrated a correlation between coagulation changes and the natural history of malignancies.…”
Section: Discussionmentioning
confidence: 85%
“…32 As in many other human malignancies, [33][34][35][36][37][38] including lung carcinoma, DD might have prognostic significance. 12,15,39 In 1993, Seitz et al 12 reported that TAT and DD were significantly increased in patients with metastatic disease and that elevated TAT values at diagnosis might be prognostically significant. Taguchi et al 15 measured the plasma levels of DD in 70 lung carcinoma patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tissue markers of fibrinolysis, mainly the levels of tissue-type (tPA) and urokinase-type (uPA) plasminogen activators, have prognostic significance in patients with localized and metastatic breast cancer (Solomayer et al, 1997). In patients with both non-small cell and small cell lung cancer, increased plasma D-dimer levels were shown to be predictive for a worse clinical outcome (Taguchi et al, 1997). Similarly in patients with primary colorectal cancer, D-dimers predicted for more advanced stage of disease and worse prognosis (Oya et al, 1998).…”
Section: Molecular and Cellular Pathologymentioning
confidence: 99%